The Bear's Lair: Index Credit Default Swaps and the Subprime Mortgage Crisis - Stanton, Richard; Wallace, Nancy (Review of Financial Studies, 2011)
During the recent financial crisis, ABX.HE index credit default swaps (CDS) on baskets of mortgage-backed securities were a benchmark widely used by financial institutions to mark their subprime mortgage portfolios to market. However, we find that prices for the AAA ABX.HE index CDS during the crisis were inconsistent with any reasonable assumption for mortgage default rates, and that these price changes are only weakly correlated with observed changes in the credit performance of the underlying loans in the index, casting serious doubt on the suitability of these CDS as valuation benchmarks. We also find that the AAA ABX.HE index CDS price changes are related to short-sale activity for publicly traded investment banks with significant mortgage market exposure. This suggests that capital constraints, limiting the supply of mortgage-bond insurance, may be playing a role here similar to that identified by Froot (2001) in the market for catastrophe insurance. The Author 2011. Published by Oxford University Press on behalf of The Society for Financial Studies. All rights reserved. For Permissions, please e-mail: journals.permissions@oup.com., Oxford University Press.